2018
DOI: 10.1155/2018/6172676
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics and Analysis of a Planar Multilink Complex Mechanism with Clearance

Abstract: In order to understand the nonlinear dynamic behavior of a planar mechanism with clearance, the nonlinear dynamic model of the 2-DOF nine-bar mechanism with a revolute clearance is proposed; the dynamic response, phase diagrams, Poincaré portraits, and largest Lyapunov exponents (LLEs) of mechanism are investigated. e nonlinear dynamic model of 2-DOF nine-bar mechanism containing a revolute clearance is established by using the Lagrange equation. Dynamic response of the slider's kinematics characteristic, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Conversely, the velocity, acceleration, and reaction force curves obtained from the two simulation models show great differences. Compared with the case that only flexible links exist, dramatic oscillations are introduced by joint clearance which can also be found in Chen et al's research [33]. It means that joint clearance has greater effects on the dynamic responses of the mechanical system.…”
Section: Simulation Results With Clearance Jointsmentioning
confidence: 78%
“…Conversely, the velocity, acceleration, and reaction force curves obtained from the two simulation models show great differences. Compared with the case that only flexible links exist, dramatic oscillations are introduced by joint clearance which can also be found in Chen et al's research [33]. It means that joint clearance has greater effects on the dynamic responses of the mechanical system.…”
Section: Simulation Results With Clearance Jointsmentioning
confidence: 78%
“…They concluded that the largest Lyapunov exponents are dependent on the clearance size and the input speed. Chen et al identified the chaos phenomenon of the 2-DOF nine-bar mechanism with a revolute clearance using the phase diagrams, the Poincaré portraits, and largest Lyapunov exponent parameter [8]. Bifurcation diagrams with changing clearance value, friction coefficient, and driving speed are drawn.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic equations of motion were derived using generalized coordinates and the Lagrange method, and the effects of clearance size and driving speed on system bifurcation were investigated. Chen [13] utilized the KED method with the Lagrange method to establish a nonlinear dynamic model of a spatially parallel mechanism. The study showed the influence of various clearances on the parallel mechanism dynamics behavior, including chaos and bifurcation phenomenon, which provided a methodology for forecasting the dynamics behavior of parallel mechanisms with clearance and flexible links.…”
Section: Introductionmentioning
confidence: 99%